Record of shallow-water sponges in Simeulue Island, Aceh Province, Indonesia - EDWIN SETIAWAN; FARID KAMAL MUZAKI; AWIK P.D. NURHAYATI; NOVA MAULIDINA (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Setiawan E, Muzaki FK, Nurhayati APD, Maulidina N. 2019. Record of shallow-water sponges in Simeulue Island, Aceh Province, Indonesia. Biodiversitas 20: 3246-3257. The first and present study on shallow water sponges in Simeulue islands, Aceh Province, Indonesia recorded more than twenty species of marine sponges. This first assessment was also part of Ekpedisi Widya Nusantara X (E-WINN X) coastal chapter 2017 where was conducted in Simeulue islands, Aceh. Most of the recorded sponges are common species that are also recognized inhabiting a broad distribution in the West Indo-Pacific marine ecoregion. All recorded shallow-water sponges are Demospongian sponges. Among the three selected types of shallow water sponge habitats, a number of sponges are achieved mostly in shallow reefs in comparison to sandy and mangrove lagoons. The current study on species recorded also documents general characteristic enriches and highlights the importance of filling the gaps in distributional patterns of sponges on the west coast of Sumatra.